Cerebral cortical microinfarcts on MRI and their association with cognition in cerebral amyloid angiopathy - Xiong, Li (Stroke, 2018)
BACKGROUND AND PURPOSE: We aimed to explore the association between presence of cerebral cortical microinfarcts (CMIs) on MRI and other small vessel disease neuroimaging biomarkers in cerebral amyloid angiopathy (CAA) and to analyze the role of CMIs on individual cognitive domains and dementia conversion. METHODS: Participants were recruited from an ongoing longitudinal research cohort of eligible CAA patients between March 2006 and October 2016. A total of 102 cases were included in the analysis that assessed the relationship of cortical CMIs to CAA neuroimaging markers. Ninety-five subjects had neuropsychological tests conducted within 1 month of MRI scanning. Seventy-five non-demented CAA patients had cognitive evaluation data available during follow-up. RESULTS: Among 102 patients enrolled, 40 patients had CMIs (39%) on MRI. CMIs were uniformly distributed throughout the cortex without regional predilection (P=0.971). The presence of CMIs was associated with lower total brain volume (OR=0.85, 95% CI: 0.74, 0.98, P=0.025) and presence of cortical superficial siderosis (OR=2.66, 95% CI: 1.10, 6.39, P=0.029). In 95 subjects with neuropsychological tests, presence of CMIs was associated with impaired executive function (β= −0.23, 95% CI: −0.44, −0.02, P=0.036) and processing speed (β= −0.24, 95% CI: −0.45, −0.04, P=0.020). Patients with CMIs had a higher cumulative dementia incidence compared to patients without CMIs (P=0.043), while only baseline total brain volume (HR=0.76, 95% CI: 0.62, 0.92, P=0.006) independently predicted dementia conversion. CONCLUSIONS: MRI-detected CMIs in CAA correlated with greater overall disease burden. The presence of CMIs was associated with worse cognitive performance, while only total brain atrophy independently predicted dementia conversion.